The influence of inquiry-based learning on high school students’ critical and creative thinking skills - Krit, Pong; Som, Rit; Chai, Som (Yayasan Adra Karima Hubbi, 2024)
The ability to think critically and creatively is essential for students to succeed in a rapidly changing world. Traditional teaching methods often fail to develop these skills in students. Inquiry-Based Learning (IBL), which encourages students to explore questions and seek solutions independently, is proposed as an effective approach to enhancing critical and creative thinking. Despite its potential, limited research exists on the impact of IBL on these skills in high school settings, particularly in non-Western educational contexts. This study aims to investigate the influence of Inquiry-Based Learning on high school students’ critical and creative thinking skills in a classroom setting. A quasi-experimental design was used, involving 120 high school students from two different schools. One group received IBL-based instruction, while the other group followed traditional teaching methods. Data were collected using pre- and post-assessments of critical and creative thinking skills, along with student surveys and classroom observations. The results revealed that students in the IBL group showed significant improvements in both critical and creative thinking skills compared to the control group. Analysis indicated that IBL encouraged greater student engagement, problem-solving, and innovative thinking. The study suggests that Inquiry-Based Learning is a promising method for enhancing high school students’ critical and creative thinking skills, offering valuable implications for educational practices.